ACSM's foundations of strength training and conditioning - Ratamess, Nicholas A (Wolters Kluwer, 2022)
"Developed by the American College of Sports Medicine (ACSM), ACSM's Foundations of Strength Training and Conditioning, 2nd Edition offers a comprehensive introduction to the basics of strength training and conditioning essential to develop, implement, and assess training programs. This text focuses on practical applications, empowering students and practitioners to develop, implement, and assess the results of training programs that are designed to optimize strength, power, and athletic performance. Clear, straightforward writing helps students master new concepts with ease, and engaging learning features throughout the text provide the understanding and confidence to apply lessons to clinical practice."--Page 4 of cover..